Analysis of Diagnostic Assessment on Fulfillment of Competency Standards in the Implementation of the 2013 Curriculum Emergency Covid 19 at Public Elementary School 3 Abepura, Jayapura City, Papua - Ali Aisyah; Sukmawati; Ristiani Ria (Journal of Educational Analytics, 2023)
This study aims to look at and analyze the strategies used in determining and selecting essential competencies in an effort to fulfill basic competencies and learning outcomes at Abepura 3 Public Elementary School, Jayapura City. This research was conducted using a descriptive-qualitative method. Data collection was carried out through interviews, observation of the elementary school situation, and literature studies relevant to the research topic. Data analysis was carried out in a qualitative, descriptive manner with three stages: presentation of data, analysis of data, and drawing conclusions. Research results how that learning 67% of teachers do assessment diagnostics, consisting of 50% conducting cognitive diagnostic assessments, 33% conducting non-cognitive diagnostic assessments, 17% conducting both assessments, and 33% not conducting assessment cognitive and non-cognitive diagnostics.